Material properties of gradient copper‐nickel alloy fabricated by wire arc additive manufacturing based on bypass-current PAW. (November 2022) - Miao, Yugang; Li, Chunwang; Zhao, Yuyang; Wu, Yifan; Liu, Ji; Wang, Ziran; Zhang, Benshun
Abstract: In this paper, the bypass-current plasma arc welding (BC-PAW) based on PAW was employed to fabricate copper-nickel (Cu-Ni) gradient thin-walled structures. The effect of forming accuracy and compositional homogeneity of the bypass current Cu-Ni structure was first verified by controlled experiments. The effect of Ni content on the microstructure and mechanical properties of Cu-Ni gradient structures fabricated using bypass current was then investigated, with a focus on grain orientation and texture analysis of the three intermediate Cu-Ni mixed gradient layers. The results showed that the use of bypass current in the additive manufacturing of Cu-Ni gradient structures can improve the forming accuracy and effectively eliminate lateral composition deviations within the gradient layers. In the Cu-Ni mixed gradient layers, the average grain size of the gradient layers decreased with increasing nickel content, and unusually large secondary grains appeared in different gradient layers. Due to the different Ni content, different degrees of amplitude modulation decomposition occurred in different gradient layers, resulting in changes of grain orientation and texture composition. Under the combined effects of solid solution strengthening, fine grain strengthening and amplitude modulation decomposition, the microhardness and tensile strength increased with increasing nickel content and then decreased, reaching a maximum near the side of the gradient composition biased toward nickel. The fracture analysis showed a transition from ductility to quasi-fracture.